EFFECTS OF PHYSICAL ACTIVITY Fast Interval Training AND PROVISION OF MELINJO SKIN EXTRACT (Gnetum gnemon) ON EXPRESSION OF URAT1 TRANSPORTER, GLUT9 AND SGLT2 IN HYPERURICEMIA INSULIN RESISTANCE - Armansyah Maulana Harahap; Yetty Machrina (JBIO: jurnal biosains (the journal of biosciences), 2022)
Observational studies and randomised controlled studies suggest Increased prevalence of hyperuricemia is a decrease in physical activity and high consumption of purines. Disruption of urate reabsorption causes changes in the main functions of transporter proteins in the proximal tubule membrane. One of them is the intake of URAT1 and efflux by GLUT9 and also for the expression of SGLT2. Insulin resistance causes disturbances in glucose uptake in (SGLT2) and urate. The mechanism of glucose uptake can be mediated by exercise and effect of melinjo skin extract. A Technical Expert Panel (TEP) of 2 medical specialist and expertise of disorder the urinary system performed the review using the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) model. The TEP planned a research on PubMed selecting “Hyperuricemia” as MeSH (Medical Subject Headings) term adding to PubMed Search Builder the terms “Exercise” and “Melinjo skin extract”. TEP is considered for eligibility articles published within the last 10 years, including original research, in particular in vitro studies, and animal and clinical studies in English. Results: Of the 90 identified studies, TEP included 15 studies, 8 animals, and 4 clinical studies and 3 Review. Conclusion: Our scoping review describes and summarizes the important role of exercise and the effect of melinjo peel extract in modulating uric acid levels, Insulin resistance and up-and-down regulation of urate transportersKeyword: Hyperuricemia, URAT1, GLUT9, SGLT2, Exercise